Fair and Equitable Treatment and the Fabric of General Principles - Palombino, Fulvio Maria (T.M.C. Asser Press, 2018)
This book moves from the circumstance whereby currently the obligation to provide fair and equitable treatment (FET) to foreign investments is included in the majority of international investment agreements and has proved to be the most invoked standard in investor-State arbitration. Hence, it is no overstatement to describe this standard as the basic norm of international investment law. Yet both its meaning and normative basis continue to be shrouded in ambiguity and, as a consequence, to inspire a considerable number of interpretations by legal writers. The book's precise aim is to unravel such ambiguity, arguing from the idea that FET has become part of the fabric of general international law, but has done so by means of a source somewhat neglected in legal doctrine. This being the category of general principles peculiar to a certain field of international law, i.e. those principles having their own foundations in the international legal order itself, but which, through the mediation of the judge, end up being shaped according to the features typical of a specific normative field. The book, as well as having a solid theoretical backdrop as its basis, offers a careful and critical analysis of pertinent case law, and will prove useful to both scholars and practitioners. Fulvio Maria Palombino is Professor of International Law at the Law Department of the University of Naples Federico II and a member of the Executive Board of the European Society of International Law.